Challenges in Automotive Electromagnetic Compatibility Modeling and Simulation - Neumayer, Roland; Weigel, Robert (Electromagnetics in a Complex World - Challenges and Perspective, 2003)
Electromagnetic compatibility (EMC) issues are increasingly important to the automotive industry. Problems arise from the growing use of electronic systems on the one hand and the lack of flexibility in placement or design of electronic modules on the other hand. Consequently, an accurate system-level EMC analysis is required from early stages of the vehicle design process. This paper presents a concurrent EMC simulation process that incorporates the EMC behavior of the electronic equipment in the system-level automotive EMC simulation. The proposed process helps to identify and reject potential EMC problems introduced by new technologies. This cuts the risk of EMC failure and avoids costly and time-consuming redesigns.
elib2cris::1512001600,neumayer2003a